1985
DOI: 10.1159/000118216
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Psychotherapeutic Effects of Anesthesia with Isoflurane (ES Narcotherapy) in Treatment-Refractory Depressed Patients

Abstract: Treatment-refractory depressed patients who objected to electroconvulsive therapy (ECT) were given a series of anesthesias with isoflurane (Forane®), a modern and established inhalation anesthetic. According to our hypothesis to be tested, the brief period of electrocerebral silence (ES), which can be observed shortly after the grand mal seizure in ECT, may be in itself a crucial biological determinant for the therapeutic effects of ECT. Isoflurane is the only drug known to effect an ES in the EEG in nontoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 6 publications
(9 reference statements)
4
35
0
Order By: Relevance
“…They treated 12 depressed patients, who had been refractory to conventional antidepressant drug treatment for many months, by a series of maximally six deep anesthesias with isoflurane. They observed rapid (within 1 h after awakening from anesthesia), reproduc ible (from one anesthesia session to another) and cumula tive (the antidepressant effect had been boosted by each anesthesia) antidepressant effects of anesthesias with iso flurane [1,4,24]. They could replicate this innovative study by consecutive studies [25], and other authors [26,27] reported similiar observations with isoflurane.…”
Section: History and Rationale O F Isonarmentioning
confidence: 93%
See 3 more Smart Citations
“…They treated 12 depressed patients, who had been refractory to conventional antidepressant drug treatment for many months, by a series of maximally six deep anesthesias with isoflurane. They observed rapid (within 1 h after awakening from anesthesia), reproduc ible (from one anesthesia session to another) and cumula tive (the antidepressant effect had been boosted by each anesthesia) antidepressant effects of anesthesias with iso flurane [1,4,24]. They could replicate this innovative study by consecutive studies [25], and other authors [26,27] reported similiar observations with isoflurane.…”
Section: History and Rationale O F Isonarmentioning
confidence: 93%
“…In their pilot study in female depressed patients, Langer et al [1] observed that very rapid, reproducible and cumulative antidepressant effects could be induced by a series of deep anesthesias with the inhalation anesthetic, isoflurane (Forane®, Abbott).…”
Section: History and Rationale O F Isonarmentioning
confidence: 99%
See 2 more Smart Citations
“…Intravenous anesthetic propofol in vitro at low micromolar concentrations activates AMPARs on VTA DA neurons . Interestingly, isoflurane anesthesia alone has been tested in treatment-refractory depressed patients and found to produce long-lasting antidepressant effect, which was similar to electroconvulsive therapy (under isoflurane anesthesia) (Langer et al, 1985(Langer et al, , 1995. These results were recently confirmed in a study on refractory depression, which also showed that electroconvulsive therapy (on an average ten 15-minute sessions within 3 weeks) had modestly more efficient antidepressant effect than isoflurane anesthesia alone at 4-week follow up, but produced more severe neurocognitive adverse effects (Weeks et al, 2013).…”
mentioning
confidence: 99%